2016
DOI: 10.1038/nature19339
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition for treatment of leishmaniasis, Chagas disease and sleeping sickness

Abstract: Chagas disease, leishmaniasis, and sleeping sickness affect 20 million people worldwide and lead to more than 50,000 deaths annually1. The diseases are caused by infection with the kinetoplastid parasites Trypanosoma cruzi, Leishmania spp. and Trypanosoma brucei spp., respectively. These parasites have similar biology and genomic sequence, suggesting that all three diseases could be cured with drug(s) modulating the activity of a conserved parasite target2. However, no such molecular targets or broad spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
371
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 348 publications
(405 citation statements)
references
References 45 publications
(52 reference statements)
8
371
0
10
Order By: Relevance
“…Interestingly, other researchers have also denoted the ability of oxazole compounds to show activity against related kinetoplastids T. brucei, T. cruzi , and leishmaniasis [35]. Nearly all of the linker replacements showed activity towards P. falciparum D6 with the pyrimidines 17 and 18 (EC 50 = 0.93 and 0.069 μM, respectively), amide 21 (0.53 μM), and 1,2,4-triazole 26 (0.21 μM) being the most potent analogs from all the compounds screened against P. falciparum D6.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, other researchers have also denoted the ability of oxazole compounds to show activity against related kinetoplastids T. brucei, T. cruzi , and leishmaniasis [35]. Nearly all of the linker replacements showed activity towards P. falciparum D6 with the pyrimidines 17 and 18 (EC 50 = 0.93 and 0.069 μM, respectively), amide 21 (0.53 μM), and 1,2,4-triazole 26 (0.21 μM) being the most potent analogs from all the compounds screened against P. falciparum D6.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts are being made to, on the one hand, standardize assays, models and screening cascades across the different investigators in the field, while on the other hand identifying and validating novel targets using new tools such as Bioluminescence Imaging (BLI), whole genome sequencing, and -omics. Knowing the target of a potential drug candidate issued from phenotypic screening could allow for better study design in vivo with a particular treatment regimen but also improved access to new chemical entities through target-based screens [64], [65]. Altogether, these new developments should lead to new potential candidates to move forward into clinical trials.…”
Section: Chagas Disease Drug Discovery and Development: A Very Dynamimentioning
confidence: 99%
“…A study 10 in 2016 identified the triazolopyrimidine molecule GNF6702 as having potent activity against Leishmania. It acts by inhibiting the cell's proteasomal protein-degradation machinery.…”
Section: Drug Candidate and Target For Leishmaniasismentioning
confidence: 99%